1987
DOI: 10.1007/bf02455991
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of yohimbine in man

Abstract: The kinetic disposition of yohimbine was examined in eight young male subjects following a single oral dose of 10 mg yohimbine hydrochloride. The drug was rapidly absorbed (absorption half-time 0.17 +/- 0.11 h) and rapidly eliminated from the plasma (elimination half-life 0.60 +/- 0.26 h). This clearance of yohimbine from plasma was constant over approximately 10 elimination half-lives, suggesting that distribution into a second pharmacokinetically distinct compartment was not responsible for the rapid decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 13 publications
2
41
1
Order By: Relevance
“…The effect of yohimbine lasted for 45 min: this duration of action compares with a halflife in man of around 0.6 h (Owen et al, 1987). This stimulating effect of yohimbine, an a2-adrenoceptor Figure 4 The effect of nerve section on the ability of yohimbine (0.5mgkg-' i.v.…”
Section: Discussionmentioning
confidence: 92%
“…The effect of yohimbine lasted for 45 min: this duration of action compares with a halflife in man of around 0.6 h (Owen et al, 1987). This stimulating effect of yohimbine, an a2-adrenoceptor Figure 4 The effect of nerve section on the ability of yohimbine (0.5mgkg-' i.v.…”
Section: Discussionmentioning
confidence: 92%
“…This observation can be explained by the short half-life of the drug: 0.6 to 1.0 h according to Owen et al (1987) and Guthrie et al (1990) although long-active metabolites were recently described (Le Verge et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The data of urinary excretion and partitioning into red blood cells revealed that the rapid plasma clearance of yohimbine may result from the metabolism (a first-pass effect) but not from the renal elimination or sequestration by red blood cells (9). Based on these findings, it is probable that the stimulatory effect of yohimbine on ejaculation in dogs is related to an active metabolite(s) of the compound.…”
Section: Discussionmentioning
confidence: 94%